2003
DOI: 10.1063/1.1615685
|View full text |Cite
|
Sign up to set email alerts
|

Using point-defect engineering to increase stability of highly doped ultrashallow junctions formed by molecular-beam-epitaxy growth

Abstract: Stability of p+/n junctions remains a critical issue for device performance. We report that the technique of point-defect engineering (PDE) can substantially increase the stability of ultrashallow junctions formed by molecular-beam epitaxy. It is shown that an as-grown 15 nm, 2×1020/cm3 B-doped Si layer becomes unstable during 10 min thermal anneal above 650 °C. The thermal stability can be increased by performing a 5×1015/cm2 1 MeV Si ion implantation. The B profile with the MeV Si implant does not show signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…With the elimination of band gap narrowing and strain as factors reducing the B diffusion, point defect engineering remains as a viable option. Shao et al [15][16][17][18] have demonstrated that it is possible to reduce boride-enhanced diffusion by injecting vacancies near the surface using MeV implantation. During the postimplant anneal the interstitials and vacancies recombine, reducing the concentration of interstitials available for B diffusion.…”
Section: Discussionmentioning
confidence: 98%
“…With the elimination of band gap narrowing and strain as factors reducing the B diffusion, point defect engineering remains as a viable option. Shao et al [15][16][17][18] have demonstrated that it is possible to reduce boride-enhanced diffusion by injecting vacancies near the surface using MeV implantation. During the postimplant anneal the interstitials and vacancies recombine, reducing the concentration of interstitials available for B diffusion.…”
Section: Discussionmentioning
confidence: 98%